Learning Management and ICT on the Learning Effectiveness: A Literature Review from Diverse Lenses - Maya Sova; Maryadi Tirtana Siregar; Iskandar Ahmaddien; Christiyanti Aprinastuti; Kristia Kristia (AL-ISHLAH: Jurnal Pendidikan, 2022)
The study aims to understand the use of Information and Communication Technology (ICT) as well as learning management which has a very important position in increasing the effectiveness of the teaching and learning process. Various obstacles, difficulties, and limitations are faced in the teaching and learning process, starting from the factors of students, students' families, as well as the use of information technology which is still not optimally and equally distributed both in terms of equipment and management. This study uses a literature review as the research method. Ten articles were the data of this study gained from the digital literature search. The data was then analysed using the content analysis method. The results reveal that it can be seen that effective learning can be applied if the learning management is structured and implemented properly by all related parties. This learning management concept had implications for Indonesian education during the COVID-19 pandemic. It cannot be separated from the use of ICT, where there are still obstacles or limitations both in terms of knowledge and existing facilities for teachers and students. These obstacles can be overcome by optimizing facilities for users and training to improve technical knowledge and use. Educators' and students’ good mastery will enable an increase in the effectiveness and efficiency of the learning process.